Traditional Herbal Medicine Discovery for the Treatment and Prevention of Pulmonary Arterial Hypertension - Xue, Zhifeng; Li, Yixuan; Zhou, Mengen; Liu, Zhidong; Fan, Guanwei; Wang, Xiaoying; Zhu, Yan; Yang, Jian (Frontiers in Pharmacology, 2021)
Pulmonary arterial hypertension (PAH) is characterized by pulmonary artery remodeling that may subsequently culminate in right heart failure and premature death. Although there are currently both non-pharmacological (lung transplantation, etc.) and pharmacological (Sildenafil, Bosentan and new oral drugs on trial) therapies available, PAH remains a serious and fatal pulmonary disease. Traditional herbal medicine (THM) treatment, as a unique medical treatment, has gradually exerted its advantages in the treatment of PAH worldwide through a multi-level and multi-target approach. Additionally, the potential mechanisms of THM were deciphered, including suppression of proliferation and apoptosis of pulmonary artery smooth muscle cells, controlling the processes of inflammation and oxidative stress, regulations of vasoconstriction, ion channels and so on. In this review, the effects and mechanisms of the frequently studied compound THM, single herbal preparations, and multiple active components from THM are comprehensively summarized, as well as their related mechanisms on the several classical preclinical PAH models. It is worth mentioning that the sodium tanshinone IIA sulfonate sodium and tetramethylpyrazine are under clinical trials and considered as the most promoting medicines for PAH treatment. Last, reverse pharmacology, a strategy to discover THM or THM-derived components has been also proposed here for PAH. This review discusses the current state towards THM, their working mechanisms against PAH and future prospects of reverse pharmacology, which is expected to facilitate the natural anti-PAH medicine discovery and development, as well as its bench to bedside transformation.